Reducing the vulnerability of tourists to tsunami: challenges for decision-makers - Fathianpour A; Wilkinson S; Jelodar MB; Evans B (Springer Nature, 2023)
A near source or local tsunami, because of its close proximity to an affected area, cannot usually be predicted soon enough to mitigate many of the risks posed. The limited notice time in local tsunamis poses greater challenges for decision-makers than distant source tsunamis. Tsunamis affect coastal regions, where many of these areas are visited by tourists who often lack adequate knowledge of the hazards of the region. This study focuses on the risks tourists face during a local tsunami and discusses how to best protect tourists. Initially, a thematic literature analysis was performed to identify research gaps. Then, a case study methodology was adopted to obtain an in-depth understanding of how emergency management officials consider the management of tourists in evacuation planning. Napier, New Zealand, was used as a case study because it is a tourist town and vulnerable to tsunamis. Key decision-makers in the disaster management and tourist management sector were interviewed. The results outline three major initiatives that could lead to better tourist management and create better tsunami awareness for tourists. First, the risks posed to tourists can be reduced if emergency management officials collaborate with tourism agencies. Second, developing accurate evacuation simulations can show what would happen to tourists in a tsunami so that emergency management officials can be better prepared, and councils can improve evacuation planning and infrastructure to evacuate tourists and local communities safely. Third, educating tourists about evacuation plans will increase their readiness and enhance their safety.